Manufacturability readiness of insulated Cu wire bonding process in PBGA package - Hungyang L.; Boonkar Y.; Yong T.C.; Khan N.; Ibrahim M.R.; Tan L.C. (Institute of Electrical and Electronics Engineers Inc., 2023)
Today, microelectronics devices are getting smaller with more I/Os. Conventional ultra fine pitch wire bonding is facing wire-to wire short and wire sweeping issues. The use of insulated Cu wire is a potential technology enabling greater wire density, and wires touching and crossing, as the wire is coated with a layer or organic coating to prevent wire-to-wire short. In this paper we analyze the reliability of insulated Cu wire with diameter of 20 ?m in PBGA package under unbiased HAST, TC and HTS reliability stressing using standard, touched wires profile and extreme loop height without kinks profile. Ball shear, wire pull and stitch pull tests as well as Cu/Al IMC thickness measurement test w performed after reliability stressing for bare Cu and insulated Cu wire samples. Results show that insulated Cu wire reliability samples show similar ball bond strength performance after the ball shear and wire pull test. Although stitch pull strength of insulated Cu is ?17% less than bare Cu samples, the reliability results indicate that insulated Cu stitch bond has good reliability. Effect of the capillary touchdowns to the ball and stitch bond integrity of bare Cu and insulated Cu wire bonding is also presented in this paper. Capillary residue build up on the tip surface was investigated. We found capillary condition and life are comparable to bare Cu wire capillary. © 2014 IEEE.